ENGLISH AS A FOREIGN LANGUAGE LEARNING DEMOTIVATIONAL FACTORS AS PERCEIVED BY SAUDI UNDERGRADUATES - Al-Khairy, Muhammad H. (European Scientific Journal, ESJ, 2013)
Motivation is an important factor that is instrumental in successfully carrying out any activity and its significance is highlighted widely by a growing mass of motivational studies conducted in the field of second as well as foreign language learning contexts. This study is an attempt to investigate the common factors that are perceived as demotivating by Saudi university undergraduates represented by the cohort of this study. The sample of this study responded to a 23-item self-structured questionnaire to record their demotivational factors towards learning English as a foreign language. The data generated were scientifically analyzed in terms of descriptive analysis and independent-samples t-test was run to indentify whether or not any significant differences exist in the responses of English-major and non English-major learners. The results reported that Saudi university undergraduates felt demotivated because of the factors which include textbooks; English faculty behaviors; peer pressure; teaching methods; insufficient use of modern teaching aids, difficult English vocabulary and grammar etc. It is suggested that teachers should use English language in classes, speak slowly to ensure understanding, avoid using Arabic, avoid losing their temper during classes, ensure that interactive activities are frequently exploited and use modern teaching facilities as much as possible to maximize the involvement of the learners in classroom proceedings for better learning. Furthermore, it is also exhorted that the English departments should rationalize English syllabus and select English textbooks after proper deliberation to cater to the learners’ interest and proficiency in the target language.